The Effect of Parenting Style on Family Emotional Regulation - Putri, Rania Herdiani; Indrianti, Adelia; Fitriani, Azma Nur; Srinayanti, Yanti; Lismayanti, Lilis; Gandara, Purnama; Rosmiati, Rosmiati (Inspirasi Foundation, 2026)
Introduction: Parenting styles significantly influence emotional regulation and psychological well-being within families. Supportive parenting enhances emotional skills, whereas unresponsive parenting may lead to tension in family relationships. Objective: This review aims to analyze the impact of parenting styles on emotional regulation within families and its implications for the emotional well-being of family members. Method: This review employed a structured search strategy across four databases, PubMed, ProQuest, Garuda, and JSTOR to identify studies on the influence of parenting styles on emotional regulation in families from 2015 to 2024. The population included parents and children, with parenting styles measured using the PSDQ and emotional regulation using the ERC. Three independent reviewers conducted the selection process following the PRISMA Flow Chart, and article quality was assessed using the CASP Checklist. Extracted data included authors, intervention types, settings, session frequency and duration, as well as the methods and media used. Result: Based on 11 studies with 6,835 participants from Indonesia, Australia, Iran, China, Nigeria, Romania, Palestine, and India, parenting styles significantly influenced emotional regulation and well-being. The authoritative style had positive effects, while permissive and authoritarian styles had negative impacts. Parental emotional regulation, education, and cultural values were moderating factors. Interactive interventions over 6-12 sessions within 4-12 weeks were most effective. Conclusion: Authoritative parenting fosters children's emotional regulation and pro-social behavior, whereas authoritarian and permissive styles are associated with negative outcomes. Therefore, parenting education and family therapy are essential to promoting authoritative parenting styles to support children's emotional well-being.